2016
DOI: 10.1016/j.procbio.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of recombinant protein expression in Escherichia coli biofilms analysed at single-cell level

Abstract: Highlights Epifluorescence microscopy and image processing enable single-cell expression analysis. Escherichia coli biofilm heterogeneity increased during biofilm development. Fluorescence heterogeneity was correlated with spatial heterogeneity. 2 AbstractBioprocesses based on surface-associated microorganisms are emerging in environmental and industrial areas owing to the physiological specificities and heterogeneities of biofilm cells. This study describes a simple and accurate method for evaluating re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Then, the biofilm was resuspended and homogenized in 25 mL of 8.5 g L −1 NaCl solution for assessment of total and viable cells and for quantification of eGFP and plasmid content. The Live/Dead ® BacLight™ bacterial viability kit (Syto9/propidium iodide; Invitrogen Life Technologies, Alfagene, Carcavelos, Portugal) was used to quantify the viability of bacterial populations as a function of the membrane integrity of the cell [45]. Results of total (viable plus non-viable) and viable cell counts were expressed as log cell•cm −2 .…”
Section: Biofilm and Planktonic Analysismentioning
confidence: 99%
“…Then, the biofilm was resuspended and homogenized in 25 mL of 8.5 g L −1 NaCl solution for assessment of total and viable cells and for quantification of eGFP and plasmid content. The Live/Dead ® BacLight™ bacterial viability kit (Syto9/propidium iodide; Invitrogen Life Technologies, Alfagene, Carcavelos, Portugal) was used to quantify the viability of bacterial populations as a function of the membrane integrity of the cell [45]. Results of total (viable plus non-viable) and viable cell counts were expressed as log cell•cm −2 .…”
Section: Biofilm and Planktonic Analysismentioning
confidence: 99%
“…It was also shown that its biofilm formation behavior is similar to other E. coli strains including a clinical isolate that is often used for antimicrobial susceptibility tests [43]. Additionally, this strain was successfully used to produce a model recombinant protein in a biofilm flow cell system [16][17][18].…”
Section: Characterizationmentioning
confidence: 99%
“…A reactor system comprising a recirculating tank (for planktonic cells), a vertical flow cell reactor (where biofilms are formed), and peristaltic and centrifuge pumps that allow the circulation of the bacterial suspension was operated as described by Gomes et al [ 25 ]. The flow cell reactor is a semi-circular Perspex duct with apertures on its flat wall to fit removable Perspex pieces (coupons) to which polyvinyl chloride (PVC) slides were glued.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli cells were grown by recirculating the bacterial suspension at 30 °C for 11 days under turbulent flow (Reynolds number of 4600) [ 25 ]. The recirculating tank was aerated using an air pump (flow rate of 108 L h −1 ) and continuously fed with lysogeny medium (LB-Miller; Sigma, St. Louis, USA) supplemented with 20 μg mL –1 kanamycin at a flow rate of 0.025 L h –1 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation